Analysis of the Implementation of Village Fund Disbursement Information System by Village Financial Management Apparatus in Penajam Paser Utara Regency - Edowar Azas Saputra; Mujahid Yunus; Abdul Samad (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2025)
This research is motivated by the need for an efficient and accountable village financial management system. Its purpose is to analyze the implementation of the Village Fund Submission and Disbursement Information System and to identify its supporting and hindering factors. This study adopted a qualitative approach. Data was collected through in-depth interviews with key informants, namely the Village Heads, Village Treasurers, and Village Financial Affairs Heads from five different villages. The research data was then analyzed thematically to identify key patterns and the essence of the informants' experiences and perceptions. The research results show that the implementation of the Village Fund and Disbursement Information System has improved the efficiency, transparency, and accountability of village financial management. This was supported by systematic procedures, adequate training, and high motivation from officials. However, implementation was hindered by unstable internet network infrastructure, technical application issues, and human resource limitations.The conclusion of this study is that while the Village Fund Disbursement Information System is highly beneficial, continuous infrastructure improvement and human resource capacity development are crucial to maximize the system's potential for effective village financial governance.